2016
DOI: 10.4093/dmj.2016.40.4.253
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Regular Exercise on Insulin Sensitivity in Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analysis

Abstract: The purpose of this study was to examine the effect of regular exercise training on insulin sensitivity in adults with type 2 diabetes mellitus (T2DM) using the pooled data available from randomised controlled trials. In addition, we sought to determine whether short-term periods of physical inactivity diminish the exercise-induced improvement in insulin sensitivity. Eligible trials included exercise interventions that involved ≥3 exercise sessions, and reported a dynamic measurement of insulin sensitivity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(104 citation statements)
references
References 43 publications
2
100
0
2
Order By: Relevance
“…Various studies of insulin-resistant patients have shown that exercise improves lipid oxidation and insulin sensitivity (Way, Hackett, Baker, & Johnson, 2016), which is probably due to the fact that exercise modulates insulin resistance through increasing the insulin receptor, glucose transport proteins (GLUT4), and glycogen synthase; improving intracellular insulin signaling; increased activity of PI3K or AKT/PKB; improved AMPK signal; and increased delivery of glucose to the muscle, (Richter & Hargreaves, 2013 in order to enhance the mitochondrial fusion process and to reduce or maintain the levels of expression of mitochondrial fission proteins (Greene et al, 2015). However, exercise training, by improving insulin sensitivity in the cells, led to a significant decrease in insulin resistance and glucose levels in rats.…”
Section: Creased the Results Of Various Studies Have Shown That The mentioning
confidence: 99%
“…Various studies of insulin-resistant patients have shown that exercise improves lipid oxidation and insulin sensitivity (Way, Hackett, Baker, & Johnson, 2016), which is probably due to the fact that exercise modulates insulin resistance through increasing the insulin receptor, glucose transport proteins (GLUT4), and glycogen synthase; improving intracellular insulin signaling; increased activity of PI3K or AKT/PKB; improved AMPK signal; and increased delivery of glucose to the muscle, (Richter & Hargreaves, 2013 in order to enhance the mitochondrial fusion process and to reduce or maintain the levels of expression of mitochondrial fission proteins (Greene et al, 2015). However, exercise training, by improving insulin sensitivity in the cells, led to a significant decrease in insulin resistance and glucose levels in rats.…”
Section: Creased the Results Of Various Studies Have Shown That The mentioning
confidence: 99%
“…An interesting observation was that almost all studies reporting on sodium recommended adequate, increased or ad libitum intakes, which is in conflict with national public health recommendations . Additionally, the benefits of physical activity for improving insulin sensitivity in adults with T2D have been analysed previously . The variability in T2D populations (eg, age, sex, diabetes duration, comorbidities) across the included studies was also beyond the scope of the present analysis and should be considered in future reviews.…”
Section: Discussionmentioning
confidence: 99%
“…75 Additionally, the benefits of physical activity for improving insulin sensitivity in adults with T2D have been analysed previously. 95 The variability in T2D populations (eg, age, sex, diabetes duration, comorbidities) across the included studies was also beyond the scope of the present analysis and should be considered in future reviews.…”
Section: Ad Libitum Energy Prescriptions Included Those In Which Partmentioning
confidence: 99%
“…The process unleashed by physical inactivity and inadequate feeding, over time, causes changes in body composition that lead to the development of diseases and comorbidities associated with them [6,9,29,30]. In this way, the excess of fat, dyslipidemias and insulin resistance can promote the accumulation of fat in the liver, known as non-alcoholic fatty liver disease [4,31].…”
Section: Discussionmentioning
confidence: 99%